A pilot survey of selenium status and its geospatial variation among children and women in three rural districts of Zimbabwe - Mutonhodza, Beaula; Chagumaira, Christopher; Dembedza, Mavis P.; Joy, Edward J. M.; Manzeke-Kangara, Muneta G.; Njovo, Handrea; Nyadzayo, Tasiana K.; Lark, R. Murray; Kalimbira, Alexander A.; Bailey, Elizabeth H.; Broadley, Martin R.; Matsungo, Tonderayi M.; et al. (Frontiers in Nutrition, 2023)
Selenium (Se) deficiency is increasingly recognized as a public health problem in sub-Saharan Africa. The current cross-sectional study assessed the prevalence and geospatial patterns of Se deficiency among children aged 6-59 months (n=741) and women of 15-49 years old (n=831) selected by simple random sampling in rural Zimbabwe (Murewa, Shamva, and Mutasa districts). Venous blood samples were collected and stored according to World Health Organization guidelines. Plasma Se concentration was determined by inductively coupled plasma-mass spectrometry. Median, Q1, and Q3 plasma Se concentrations were 61.2, 48.7, and 73.3 μg/L for women and 40.5, 31.3, and 49.5 μg/L for children, respectively. Low plasma Se concentrations (9.41 μg/L in children and 10.20 μg/L in women) indicative of severe Se deficiency risk was observed. Overall, 94.6 % of children and 69.8 % of women had sub-optimal Se status defined by plasma Se concentrations of <64.8 μg/L and <70 μg/L, respectively. High and widespread Se deficiency among women and children in the three districts is of public health concern and might be prevalent in other rural districts in Zimbabwe. Geostatistical analysis by conditional kriging showed a high risk of Se deficiency and that the Se status in women and children in Murewa, Shamva, and Mutasa districts was driven by short-range variations of up to ⁓12 km. Selenium status was homogenous within each district. However, there was substantial inter-district variation, indicative of marked spatial patterns if the sampling area is scaled up. A nationwide survey that explores the extent and spatial distribution of Se deficiency is warranted.